2015
DOI: 10.1016/j.jams.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Electroacupuncture in Obese Zucker Diabetic Fatty Rats: Adiponectin and Leptin in Serum and Adipose Tissue

Abstract: Fasted, male, obese, Zucker, diabetic fatty rats aged 10-16 weeks were anesthetized with 1% halothane in nitrous oxide-oxygen (3:1) on alternate weekdays over 2 weeks. Group 1 (n = 4) did not receive electroacupuncture (controls); Group 2 (n = 4) received electroacupuncture using the Zhongwan and the Guanyuan acupoints; Group 3 (n = 4) received electroacupuncture using the bilateral Zusanli acupoints; Group 4 (n = 6) received neither halothane in nitrous oxide:oxygen nor electroacupuncture. At the end of study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…S3 ). This was in concurrence with earlier reports that have shown, diet rich in high saturated fats and sugars modulates the ratio of adiponectin:leptin & HDL-C/Total-C resulting in altered glucose & lipid metabolism and development of obesity associated co-morbidities 47 , 48 . The study thus clearly showed the vulnerability of WNIN to develop obesity, which may be due to genotype-diet interaction by epigenetic mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…S3 ). This was in concurrence with earlier reports that have shown, diet rich in high saturated fats and sugars modulates the ratio of adiponectin:leptin & HDL-C/Total-C resulting in altered glucose & lipid metabolism and development of obesity associated co-morbidities 47 , 48 . The study thus clearly showed the vulnerability of WNIN to develop obesity, which may be due to genotype-diet interaction by epigenetic mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…The beneficial therapeutic effects of acupuncture treatment could attribute to the regulation on lipid metabolism. A study using Obese Zucker Diabetic Fatty Rats reported that repeated acupuncture at Zhongwan (CV12) and Guanyuan (CV4) acupoints caused an increase in adiponectin and a decrease in leptin [52]. Recently, another study also demonstrated that acupuncture lowered the weight of visceral white adipose tissue (WAT) and increased the levels of protein pPKA, pPKC, pERK and TRPV1 in DRG and SC [53].…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
“…Acupuncture group: starting from week 12, rats in the acupuncture group were given acupuncture treatment daily for 60 consecutive days. Zusanli (ST36, 5 mm lateral to the anterior tubercle of tibia [ 30 ], bilateral), Zhongwan (CV12, 9/14 above the pubic crest of the distance measured between the top of the xiphoid process and the pubic crest [ 30 ]), and Pishu (BL20, lateral to the lower border of the 11th thoracic vertebra in the back [ 31 ], bilateral) acupoints were selected. Rats were lightly immobilized, and the acupuncture needles (Suzhou Medical Appliance Factory; 0.25 mm × 15 mm) were inserted to a depth of 3 mm at the acupoints and retained for 15 min.…”
Section: Methodsmentioning
confidence: 99%